Serum carotenoids, vitamins A and E, and 8 year lung function decline in a general population. Issue 4 (24th March 2006) - Guénégou, A; Leynaert, B; Pin, I; Le Moël, G; Zureik, M; Neukirch, F
Abstract : Background: Oxidative stress is thought to have a major role in the pathogenesis of airway obstruction. A study was undertaken to determine whether subjects with low levels of antioxidants (serum β-carotene, α-carotene, vitamins A and E) would be at a higher risk of accelerated decline in forced expiratory volume in 1 second (FEV1 ) as their lungs would be less protected against oxidative stress. Methods: 1194 French subjects aged 20–44 years were examined in 1992 as part of the European Community Respiratory Health Survey (ECRHS); 864 were followed up in 2000 and 535 (50% men, 40% lifelong non-smokers) had complete data for analysis. Results: During the 8 year study period the mean annual decrease in FEV1 (adjusted for sex, centre, baseline FEV1, age, smoking, body mass index and low density lipoprotein cholesterol) was 29.8 ml/year. The rate of decrease was lower for the subjects in tertile I of β-carotene at baseline than for those in the two other tertiles (−36.5 v −27.6 ml/year; p = 0.004). An increase in β-carotene between the two surveys was associated with a slower decline in FEV1 . No association was observed between α-carotene, vitamin A, or vitamin E and FEV1 decline. However, being a heavy smoker (⩾20 cigarettes/day) in combination with a low level of β-carotene or vitamin E was associated with the steepest decline in FEV1 (−52.5 ml/year, p = 0.0002 and −50.1 ml/year, p = 0.010, respectively). Conclusions: These results strongly suggest that β-carotene protects against the decline in FEV1 over an 8 year period in the general population, and that β-carotene and vitamin E are protective in heavy smokers.